The efficacy of manual therapy and exercise for different stages of non-specific low back pain: an update of systematic reviews. (May 2014) - Hidalgo, Benjamin; Detrembleur, Christine; Hall, Toby; Mahaudens, Philippe; Nielens, Henri
<x content-type="archive" xml:space="preserve">Abstract</x> Objective: to review and update the evidence for different forms of manual therapy (MT) for patients with different stages of non-specific low back pain (LBP). Data sources: MEDLINE, Cochrane-Register-of-Controlled-Trials, PEDro, EMBASE. Method: A systematic review of MT with a literature search covering the period of January 2000 to April 2013 was conducted by two independent reviewers according to Cochrane and PRISMA guidelines. A total of 360 studies were evaluated using qualitative criteria. Two stages of LBP were categorized; combined acute–subacute and chronic. Further sub-classification was made according to MT intervention: MT1 (manipulation); MT2 (mobilization and soft-tissue-techniques); and MT3 (MT1 combined with MT2). In each sub-category, MT could be combined or not with exercise or usual medical care (UMC). Consequently, quantitative evaluation criteria were applied to 56 eligible randomized controlled trials (RCTs), and hence 23 low-risk of bias RCTs were identified for review. Only studies providing new updated information (11/23 RCTs) are presented here. Results: Acute–subacute LBP: STRONG-evidence in favour of MT1 when compared to sham for pain, function and health improvements in the short-term (1–3 months). MODERATE-evidence to support MT1 and MT3 combined with UMC in comparison to UMC alone for pain, function and health improvements in the short-term. Chronic LBP: MODERATE to STRONG-evidence in favour of MT1 in comparison to sham for pain, function and overall-health in the short-term. MODERATE-evidence in favour of MT3 combined with exercise or UMC in comparison to exercise and back-school was established for pain, function and quality-of-life in the short and long-term. LIMITED-evidence in favour of MT2 combined with exercise and UMC in comparison to UMC alone for pain and function from short to long-term. LIMITED-evidence of no effect for MT1 with extension-exercise compared to extension-exercise alone for pain in the short to long-term. Conclusion: This systematic review updates the evidence for MT with exercise or UMC for different stages of LBP and provides recommendations for future studies.